Comparison of sagittal condylar guidance obtained from radiographic and clinical records in dentate patients - Ñahuincopa-Ríos, Richard Jesús (2021)
Objective: To compare the angle of the sagittal condylar guidance obtained from the radiographic and clinical records of dentate patients. Materials and Methods: The sample consisted of 32 patients in whom strict lateral radiography and positional records were performed: in centric relation, protrusive recording 5 mm in right laterality and protrusive recording 5 mm in left laterality. With the positional registration of the facebow, the upper model was articulated, while the lower model was articulated with the positional registration in centric relation, and with the protrusive lateral registrations on the right and left side the condylar guidance was obtained for programming the semi-adjustable articulator. Statistics were performed with the SPSS program version 24 in Spanish. Normality was evaluated using the Shapiro-Wilk test, for data with normal distribution, and the Student's T test and Pearson's correlation were performed in descriptive statistics. Results: The statistical analyses showed that gender and age influence the angle measurement of the sagittal condylar guide. The radiographic method presented a condylar guide angle of 35.69 ± 5.18, being 35.69 ± 5.16 with the clinical method (p> 0.05). Pearson's correlation test showed an important correlation between the two methods (r = 0.948, p <0.001). Conclusions: There is a high correlation in the measurements obtained from the angle of the sagittal condylar guide and the radiographic and clinical records, indicating that both methods are effective.